Community and abundance of heterotrophic diazotrophs in the northern South China Sea: Revealing the potential importance of a new alphaproteobacterium in N2 fixation. (January 2019) - Chen, Tien-Yi; Chen, Yuh-ling Lee; Sheu, Der-Shyan; Chen, Houng-Yung; Lin, Yen-Huei; Shiozaki, Takuhei
Abstract: The present study quantified nifH gene abundances of heterotrophic diazotrophs by qPCR in the northern South China Sea (SCS), a region where primary productivity and new production supported by N2 fixation are highest in the winter and unicellular N2 -fixers contribute more to nitrogen budget than filamentous N2 -fixers. Vertical distributions and seasonal abundances of four prevailing Proteobacteria, two novel α-Proteobacteria (named Alpha 1 and Alpha 2), and two γ-Proteobacteria (γ-24774A11 and Gamma 4) were investigated. The Proteobacteria accounted for 77% of the overall nifH clone library. Both Alpha 1 and Alpha 2 were distributed between 0 and 1000 m depths, while γ-Proteobacteria were concentrated mainly in the upper 200 m. Water-column abundances of Alpha 1, with a maximum of 10 9 copies m −2, were 1–2 orders of magnitude greater than Alpha 2 or γ-Proteobacteria. Alpha 1 and γ-24774A11 were most abundant in the winter and summer, respectively. Together with UCYN-A and UCYN-B, they were the most important N2 -fixers in the northern SCS. Our results suggested that diazotrophic activity of heterotrophic Proteobacteria should be considered an integrated part of nitrogen cycle in oceanic systems in which unicellular diazotrophs prevail over filamentous diazotrophs in N2 fixation. Highlights: Proteobacteria could be major N2 fixers in oligotrophic oceans. Oceanic Proteobacteria could outnumber unicellular cyanobacteria in nifH pool. Oceanic Proteobacteria show different seasonal and vertical distributions. Proteobacteria could distribute to a depth of 1000 m.